Skepticism and Philosophy in Jorge Luis Borges - Santos Gómez, Marcos (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
We present and discus the controversial philosophical view which is in the work of J. L. Borges. Fundamentally, the writer plays from an ironic and poignant skepticism that links to approaches such as hermeneutics, intertextuality and the thought of the difference (Derrida). He has been associated also with forms of structuralism and with the dissolution of the subject and identities.
Keywords: Derrida; skepticism; hermeneutics; intertextuality; JL Borges; literature; postmodernism; subjectivism